2019
DOI: 10.4293/jsls.2019.00044
|View full text |Cite
|
Sign up to set email alerts
|

Experience With Transitioning From Laparoscopic to Robotic Right Colectomy

Abstract: Background and Objectives:The number of robotic colorectal procedures performed has rapidly increased, but there are only sparse data available about the robotic learning curve of expert laparoscopic colorectal surgeons. Methods:In this retrospective study, we reviewed 101 minimally invasive right colectomies consecutively performed by a single surgeon with 20 years of clinical practice fully dedicated to laparoscopic surgery. Thus, the last 59 laparoscopic resections were compared with the first 42 robotic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…They reported that after surgeons completed their first 27 cases, a decrease in iatrogenic complications was observed, and this trend continued as the case volume increased. Gerbaud et al further reported that the transition from laparoscopic to robot-assisted colectomy with intracorporeal anastomosis may not entail any increase in the morbidity rate or reduce the oncologic quality of the surgery when performed by a surgeon with experience in laparoscopic surgery [22]. Overall, the robotic surgical system may have some technical advantages when compared with the conventional laparoscopy which ultimately benefited the patients.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that after surgeons completed their first 27 cases, a decrease in iatrogenic complications was observed, and this trend continued as the case volume increased. Gerbaud et al further reported that the transition from laparoscopic to robot-assisted colectomy with intracorporeal anastomosis may not entail any increase in the morbidity rate or reduce the oncologic quality of the surgery when performed by a surgeon with experience in laparoscopic surgery [22]. Overall, the robotic surgical system may have some technical advantages when compared with the conventional laparoscopy which ultimately benefited the patients.…”
Section: Discussionmentioning
confidence: 99%
“…After detailed treatment of the remaining studies, 5 other studies were excluded. Finally, 10 studies were included in our meta-analysis [1,2,5,8–14] Table 1. summarized the baseline characteristics and assessments for 10 studies.…”
Section: Resultsmentioning
confidence: 99%
“…The robotic platform has revolutionized minimally invasive right hemicolectomy and primary anastomosis by enabling the transition from ECA to ICA [18–20]; with a stapled ICA, robotic anastomosis is now considered to be the gold standard [13]. The ongoing development of robotic stapling technology enhances the utility and application of stapled ICA.…”
Section: Discussionmentioning
confidence: 99%